2015
DOI: 10.1136/annrheumdis-2015-eular.6081
|View full text |Cite
|
Sign up to set email alerts
|

FRI0581 Utility of the Glasgow Prognostic Score in Systemic Lupus Erythematosus, In a Single Center Cohort of 130 Patients

Abstract: BackgroundGlasgow Prognostic Score (GPS) is a simple, systemic inflammation-based prognostic score used mostly in oncology and intensive-care.ObjectivesWe aimed to investigate the utility of GPS in assessing disease activity in patients with systemic lupus erythematosus (SLE).MethodsPatients admitted consecutively to our department were prospectively enrolled in the study. Clinical and biological parameters were assessed in each participant. Disease activity was quantified using Systemic Lupus Erythematosus Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In SLE patients, GPS was correlated with disease activity. 49 Although slightly to moderately increased levels seem to be frequently observed in active lupus, 47 CRP is not one of the recommended tools in SLE disease activity follow-up, [32][33][34] as its kinetics does not seem to be similar in all SLE patients. Mok et al 50 found detectable hsCRP in almost 80% of SLE patients with active clinical manifestations, but stronger associations were observed only in cases presenting with serositis, musculoskeletal, and/or hematological involvements.…”
Section: C-reactive Protein and Erythrocyte Sedimentation Rate Discordance In Patients With Systemic Lupus Erythematosusmentioning
confidence: 99%
See 1 more Smart Citation
“…In SLE patients, GPS was correlated with disease activity. 49 Although slightly to moderately increased levels seem to be frequently observed in active lupus, 47 CRP is not one of the recommended tools in SLE disease activity follow-up, [32][33][34] as its kinetics does not seem to be similar in all SLE patients. Mok et al 50 found detectable hsCRP in almost 80% of SLE patients with active clinical manifestations, but stronger associations were observed only in cases presenting with serositis, musculoskeletal, and/or hematological involvements.…”
Section: C-reactive Protein and Erythrocyte Sedimentation Rate Discordance In Patients With Systemic Lupus Erythematosusmentioning
confidence: 99%
“…In SLE patients, GPS was correlated with disease activity. 49…”
Section: C-reactive Protein and Erythrocyte Sedimentation Rate Discordance In Patients With Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Modified Glasgow Prognostic Score (mGPS), based on the level of serum CRP and albumin (Table 1 ), has been effectively used for predicting the outcome of gastrointestinal cancer 16 . Moreover, mGPS has been used in other diseases like systemic lupus erythematosus (SLE) and acute decompensated heart failure (ADHF) 17 , 18 . It provides more prognostic information in terms of the severity and prognosis for malignant tumor compared to the neutrophil lymphocyte ratio (NLR) and platelet lymphocyte ratio (PLR), which have been widely used in IBD 19 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The sample size was calculated according to the cut-off values of inflammatory biomarkers ROC curves published in previous studies [ 3 , 4 , 5 , 6 , 7 , 8 ]. 50% of reduction/normalisation of pathological biomarkers (50 to 100%) was assumed.…”
Section: Methodsmentioning
confidence: 99%
“…Described by Glotzer et al in 1981 [ 2 ], it is characterized by endoscopic findings such as mucosal friability, oedema, erythema, appearance of polyps, ulcers, stenosis, and microscopic findings such as lymphoid follicular hyperplasia, infiltration of the lamina propria by lymphocytes, eosinophils, the appearance of plasma cells, architectural disruption, and the appearance of crypt abscesses [ 1 ]. Chronic inflammation produces an increase of serum biomarkers, like other systemic inflammatory diseases such as gastrointestinal tumour, systemic lupus erythematosus, inflammatory bowel disease and cardiovascular disease [ 3 , 4 , 5 , 6 ]. The Glasgow Pronostic Score (GPS) and its modified scale (mGPS) were used to quantify the inflammatory state, based on serum levels of C-reactive protein (CRP) and albumin [ 7 ].…”
Section: Introductionmentioning
confidence: 99%